2020
DOI: 10.1038/s41598-020-57606-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in IL17A and serum levels of IL-17A are associated with COPD related to tobacco smoking and biomass burning

Abstract: IL-17A is an important pro-inflammatory cytokine involved in the inflammatory response in chronic obstructive pulmonary disease (COPD). To evaluate the role played by single nucleotide polymorphisms of IL17A and protein levels in susceptibility to COPD, 1,807 subjects were included in a case-control study; 436 had COPD related to tobacco smoking (COPD-S) and 190 had COPD related to biomass burning (COPD-BB). Six hundred fifty-seven smokers without COPD (SWOC) and 183 biomass burningexposed subjects (BBES) serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
0
11
1
1
Order By: Relevance
“…In COPD related to cigarette smoke exposure, higher frequency of CD4+ Th17 cells and level of IL-17A in peripheral blood was described comparing with COPD with biomass-burning exposure. 53,54 However, we found no distinct difference of distribution of smokers and non-smokers among three clusters in our study (as shown in Table 2), no difference of cytokine levels between patients with and without smoking history, either (as shown in Table S3). Moreover, some researchers showed the altered IL-17A production related to functional single nucleotide polymorphism (SNP) in promotor of IL-17A gene.…”
Section: Discussioncontrasting
confidence: 55%
“…In COPD related to cigarette smoke exposure, higher frequency of CD4+ Th17 cells and level of IL-17A in peripheral blood was described comparing with COPD with biomass-burning exposure. 53,54 However, we found no distinct difference of distribution of smokers and non-smokers among three clusters in our study (as shown in Table 2), no difference of cytokine levels between patients with and without smoking history, either (as shown in Table S3). Moreover, some researchers showed the altered IL-17A production related to functional single nucleotide polymorphism (SNP) in promotor of IL-17A gene.…”
Section: Discussioncontrasting
confidence: 55%
“…Ponce-Garrez et al showed an association between a polymorphism in the cytokine IL-17A and lung disease development. Additionally, this group found increased IL-17 serum levels in all smokers, independent of COPD development 32 . These results support our previous findings that showed significantly increased IL-17+ cell density in the small airways of smokers with or without COPD.…”
Section: Discussionmentioning
confidence: 74%
“…The Th17 response has been extensively described as playing a pivotal role in autoimmune diseases 31 and more recently in COPD development and progression 32 . Ponce-Garrez et al showed an association between a polymorphism in the cytokine IL-17A and lung disease development.…”
Section: Discussionmentioning
confidence: 99%
“…Four SNPs across IL-17A, viz., rs8193036(C > T), rs8193037(G > A), rs2275913(G > A), and rs3748067(C > T) loci, located in the promoter region or 3′ UTR were examined in this study due to their considerable associations with various malignancies, including NSCLC, and chronic inflammatory respiratory diseases, such as chronic obstructive pulmonary disease, in previous studies [ 18 , 19 , 20 , 26 , 27 ]. Peripheral blood samples from LUAD patients were collected in EDTA-containing tubes for genomic DNA extraction using the QIAamp DNA Blood Mini kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%